A review of current status, challenges, and solution to improve waste management - Zhu Hang, Goh; Hadibarata, Tony (Universitas Nahdlatul Ulama Surabaya, 2022)
Government plays the most important role in improving the waste management system. Incineration system can be introduced into the waste management system to incinerate specific type of waste. This will increase the availability space for the landfilling process. However, the incineration process must be carried out with full pollution control system to prevent and minimize the pollution that might cause during the incineration process. Other than that, the government should encourage the public to separate out the waste into different categories before the collection of the waste by the waste management company. This can be implemented by providing guideline for the separation of waste methods as well as encouraging the public to be responsible for own produced waste. The dumpsites must also be improved and it is suggested that all dumpsites used are engineered sanitary landfill. An engineered sanitary landfill will reduce the impact of the pollution towards the environment to the minimum. Better tools also must be included in the sanitary landfill system to monitor the condition of the landfill site. This will prevent the happen of any unexpected conditions and can be resolve before the happening of the unexpected condition. Last but not least, the government should implement new charging fee system for the waste management. The charging fee should be based on the rate of waste generated but not flat pricing. This will help in reducing the waste generated as all individuals must pay for their own generated waste. The earth belongs to everyone which indicates everyone have the responsible to keep the earth clean and to reduce the waste produce.